Clinical characteristics of children with epilepsy managed at a tertiary hospital in Africa: a retrospective study. (2019) - Samia, Pauline; Barr, Arwen; Levi, Subira B; Donald, Kirsten A; Wilmshurst, Jo M; Newton, Charles R.
No abstract available